TINJAUAN TENTANG PERSEPSI TAMU TERHADAP MENU SUP DI CERENTI RESTORAN PADA HOTEL GRAND ZURI PADANG - Nada Wadhiah; Rasyidin Rasyid; Yulia Mandasari (Jurnal Pariwisata Bunda, 2022)
This research is motivated by the existence of a widow's soup menu that makes guests at Cerenti Grand Zuri restaurant interested. Widow's soup has become popular at the restaurant. The purposes of this study were 1) to investigate guests' responses to the soup menu at the Cerenti Grand Zuri restaurant, Padang hotel, 2) to find out why guests chose the Widow Soup menu at the Cerenti Grand Zuri restaurant at Padang hotel. The research method used was descriptive analysis. Data collection techniques used were observation, questionnaires and literature study. The results of this study indicated that the soup menu that is the most favorite is the Widow soup menu.  Guests who ordered widow soup  were not only interested by its  unique name but also its good taste. The soup menu that became the second favorite was Soto Padang.  This soup menu has a rich taste of spices and the addition of potato cakes which makes this soup menu widely ordered by guests who come to Cerenti restaurant.